Use of central venous catheter in patients hospitalized in an intensive care unit - Oliveira, Francisca Jane Gomes; Siqueira, Julianna de Freitas; Ramos, Islane Costa; Campos, Francimary de Alencar; Oriá, Mônica Oliveira Batista; Caetano, Joselany afio (Rev Rene, 2013)
This is an exploratory, descriptive study with a quantitative approach, which aimed at describing the use of central venous catheters for a short period in an intensive care unit regarding their insertion, maintenance, and removal, and at identifying the profile of patients who received the catheter in the period from June to December 2012, in a private hospital in Fortaleza, CE, Brazil. Data were collected through a questionnaire filled in with information contained in the medical records of the patients and their observation. The types of catheter used were double lumen catheter (76%), single lumen catheter (24%) and the puncture site accesses were in the subclavian vein (64%) and in the jugular vein (36%). Among the reasons for the catheter removal, these were observed: hospital discharge (44%), time of use of catheter (32%). For the maintenance of the catheter the permanent education of the health professional is important, a strategy which qualifies DOI:https://doi.org/10.15253/2175-6783.2013000500006